Characterisation of Asphaltenes Extracted from an Oil Sand and Two Petroleum Vacuum Residues Using HRTEM. (May 2017) - Zheng, Ce; Zhu, Mingming; Zhang, Dongke
Abstract: This paper reports findings from a preliminary study into the stacking characteristics of asphaltenes extracted from an oil sand and two petroleum vacuum residues. The stacking morphology was examined using high resolution transmission electron microscopy (HRTEM). The stacking parameters of the three samples including the average stacking number, the average interlayer spacing and the average layer size were estimated. The results showed that the asphaltenes extracted from the petroleum vacuum residues possessed higher stacking numbers with smaller interlayer spacing as compared to the asphaltene from the oil sand. This indicates that the intermolecular forces of the petroleum vacuum residue asphaltenes are stronger than that of the oil sand. The average layer size across the samples is ca. 0.9 nm, implying the average PAH size of 6∼7 fused rings for all samples.